Phraseology and Idiomatic Expressions in English and Russian: A Corpus-Based Comparative Study - Fayziyev Alisher (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
This article explores the similarities and differences between phraseological units and idiomatic expressions in English and Russian. Utilizing corpora such as the British National Corpus (BNC) and the Russian National Corpus (RNC), this study investigates the frequency, semantic variability, and cultural significance of idiomatic expressions in both languages. By analyzing idioms across various contexts, the research demonstrates how idiomatic expressions function as markers of cultural identity and linguistic uniqueness. Furthermore, it provides insights into the translatability of idioms and the extent to which they reveal distinct cognitive and cultural patterns. The findings indicate that while both languages share common cognitive metaphors, their idiomatic usage reflects deep-rooted cultural and linguistic particularities.